Policy Of Wonogiri Tourism Object Regional Technical Implementation Units In Tourism Development In The Covid-19 Pandemic Time In Wonogiri District - Setyawardani, Tri; Suharno, Suharno; Dewi, Nourma (International Journal of Educational Research & Social Sciences, 2022)
The background of the problems raised in this legal research is the outbreak of the Covid-19 pandemic which has an impact on various government sectors, one of which is the tourism sector, because of this pandemic, local revenue has decreased due to tourism in Wonogiri that seems very quiet. during the Covid-19 pandemic. This legal research aims to explain the various impacts arising from the Covid-19 pandemic disaster for tourism objects in Wonogiri Regency and also to explain the policies carried out by the Regional Technical Implementation Unit) in developing tourism objects in Wonogiri Regency in the midst of the Covid-19 pandemic. The research method used in this legal research is descriptive qualitative method. The results of this study explain that the important role of the Regional Technical Implementation Unit under the auspices of the Data of the Youth and Sports and Tourism Service to issue policies as a strategy for developing tourism objects in Wonogiri Regency during the Covid-19 pandemic so that the mobility of the tourism sector in Wonogiri keep going well.